(untitled) (Морфологія / Morphologia / Morfologìâ, 2021)
Background. Paclitaxel-induced peripheral neuropathy (PIPN) is a major side effect of paclitaxel in patients with cancer with no fully known mechanisms. The aim of the study was to investigate the fine sub-microscopic structure of the spinal cord anterior horn neurons in PIPN combined with 2-ethyl-6-methyl-3-hydroxypyridine succinate administration. Methods. The experiment was performed on 80 white rats, which were administered intraperitoneally with Paclitaxel (Actavis, Romania), pre-dissolved in an isotonic saline at a dose of 2 mg / kg body weight four times a day to achieve a dose of 8 mg / kg. Then 48 of these animals were injected intraperitoneally 2-ethyl-6-methyl-3-hydroxypyridine succinate at a dose of 10 mg / kg (32 rats received intraperitoneally water for injection). Observation periods were 1, 7, 14, 21, 28 days. Results. We found that 2-ethyl-6-methyl-3-hydroxypyridine corrects the morpho-functional state of the motor neurons of the spinal cord and revealed a positive metabolic effect on them. Conclusion. This was manifested by the improvement of the electron microscopic picture of the neuronal structures responsible for their protein-synthetic (granular endoplasmic reticulum, ribosomes and polysomes), respiratory (mitochondria), and protective (lysosomes) functions.